ANALISIS SEGMEN PENGGUNA PRODUK SHAMPOO HEAD & SHOULDERS DI WILAYAH KECAMATAN KALIWUNGU KENDAL - Dian Mustikorini; Umar Chadhiq (Universitas Wahid Hasyim, 2009)
Market segmentation helps marketers to define requirements and wants of consumers appropriately. The aim is to provide market segmentation best service to each segment and provide satisfaction to organizations within these segments. With so Marketers can make a profit, customer satisfaction and business sustainability. Yet constantly changing market, consumers changed and changed the competition map. Direction marketing of products typically use one or more characteristics in market segmentation. Such characteristics include segmentation demographic, psychographic and behavioral. In the midst of competition anti-dandruff shampoo sharp and the opportunity is still wide, required market segments to position the product. With market segmentation, on Head & Shoulders shampoo finally able to compile a mix strategy appropriate marketing by segmenting its market. Keywords: Market segmentation, analisys clusters, customer of loyality